A comparison of the open reduction-internal fixation and resection arthroplasty techniques in treatment of Mason Type 3 radial head fractures - Yunus Emre Akman; Erhan Sukur; Esra Circi; Osman Nuri Ozyalvac; Fatih Ozyer; Yusuf Ozturkmen (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to retrospectively compare a series of patients surgically treated with ORIF or early resection arthroplasty due to isolated comminuted radial head fractures. Methods: Between the years 2009 and 2013, 34 patients with isolated comminuted fractures of the radial head (Mason Type 3) had been operated (ORIF in 19 patients, resection arthroplasty in 15 patients). The mean age of the patients in the ORIF group was 38.5 years and 54 years in the resection group. The carrying angle (CA) and ulnar variance were measured bilaterally, and radiographs were reviewed for degenerative elbow arthritis. The Mayo elbow performance score, Turkish version of the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH-T) and visual analog scale (VAS) were used to evaluate the clinical results. Results: The mean follow-up period in the ORIF group was 40.2 months and 44.4 months in the resection group. In the ORIF group, 11 patients were clinically rated excellent, six good, and two fair. In the resection group, seven patients had excellent, five had good, and two had fair scores. We did not find a statistically significant difference between the ORIF and resection groups regarding the clinical and radiological outcomes. Conclusion: With these short-term results, resection arthroplasty may be considered an effective method in the treatment of isolated comminuted radial head fractures, as it is less technically demanding and it also allows for early postoperative motion. However, the patients should be evaluated in detail, regarding ligamentous injuries prior to resection arthroplasty. Level of evidence: Level III, Therapeutic study. Keywords: Comminuted, Isolated, Open reduction-internal fixation, Radial head fracture, Resection arthroplasty